Effect of Zilpaterol and Ractopamine on biometric parameters and muscle fiber thickness in Pelibuey lambs - Rivera-Alegria, Flor de Maria; Téllez-Medina, Dario I.; Cardador-Martínez, Anaberta; Cruz-Hernández, Aldenamar; Álvarez- González, Carlos Alfonso; Piña-Gutiérrez, José M.; Jiménez-Martínez, Cristian (Ecosistemas y Recursos Agropecuarios, 2022)
The objective of this study is to evaluate the effect of b-agonists (BA), Zilpaterol Hydrochloride (ZH), and Ractopamine Hydrochloride (RH) on the biometric parameters and the muscle fiber thickness in Pelibuey lambs (n = 6). The control group was fed a standard diet (16% protein content and 12 MJ per day); treatment groups received a standard diet supplemented with ZH or RH for 37 days and was assessed presence of BA in samples of muscle tissues, and urine. The effect of Daily Weight Gain (DWG) and Food Conversion Rate (FCR) on muscle fiber thickness was determined by Scanning Electron Microscopy (SEM) and Digital Image Analysis (DIA). Results showed an increase of 30% in DWG in the ZH group, compared with RH. While FCR was lower in ZH (3.83) than in RH (4.85). In both BA treatments, the withdrawal time was sufficient to minimize drug concentration in meat. In contrast with the control group, muscle fiber thickness increased in BA treated groups (ZH = 69.2%, and RH = 15.6%). In conclusion, ZH displayed a higher carcass yield in Pelibuey lambs.